AUDA-NEPAD Food Systems Programme Design Workshop - Neely, Constance; Chesterman, Sabrina; Gosling, Amanda; Escudero, Arthur Getz; Mutamba, Manyewu (African Union Development Agency, 2023)
This PowerPoint slide deck was developed for the AUDA-NEPAD Sustainable Food Systems Programme Design Workshop. The workshop was aligned with the implementation of recommendations of the 2021 Africa Common Position on Food Systems and the Comprehensive Africa Agriculture Development Programme (CAADP) framework. The workshop was the first of a series of planned workshops on this topic. The objective of the workshop was to outline key elements of a continental programme to support African Union Member States in implementing their priority programmes and pathways as expressed in submissions to the United Nations Food Systems Summit (UNFSS) in 2021. The slides provide context on Africa's agri-food systems by presenting summaries of the Africa Common Position and the UNFSS Dialogues. The agri-food system concept is elaborated in the context of climate change emissions reduction and adaptation along with transformative actions and pathways and a variety of game changing solutions. Slides are provided for developing a theory of change, the use of foresight planning tools (vision, root cause analysis, scenarios and backcasting) with examples and the importance of tailoring solutions to the country context to achieve the desired impact. A draft Theory of Change for Climate Resilient Food Systems from impact statement to outputs stage is provided as an example The slide deck also provides related models and frameworks of food systems as well as an indicative model for a markets based approach to resilient food systems.